Strategi Komunikasi Mengelola Persepsi Publik dalam Rebranding ACE Hardware ke AZKO - Anandianskha, Sawaviyya (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
Rebranding is a crucial strategy for companies to maintain relevance andcompetitiveness in an ever-evolving market. PT Aspirasi Hidup Indonesiaunderwent a significant rebranding effort by changing its name and brandidentity from ACE Hardware to AZKO. The primary objective was toidentify the key messages crafted within the rebranding communicationstrategy, including the elements used to build AZKO's new brand image. Aqualitative approach with a descriptive method was applied through directobservation, document analysis, and literature review. Findings revealthat AZKO's rebranding communication focused on three core elements:innovation, inspiration, and local relevance. The message